Strategic model and its impact on the commercial management of an PYME company in the automotive sector [Modelo estratégico y su impacto en la gestión comercial de una empresa PYME del sector automotriz] - Florián Castillo, Odar R. (2020)
ABSTRACT The objective of the research was to determine the impact of a strategic model on the commercial management of an Pyme company in the automotive sector. The study was preexperimental pre-test and post-test. The population being 9277 customers and 34513 sales records. A reliable questionnaire (Cronbach's Alpha of 0.883) and validated by expert judgment was applied to 137 clients. The financial statements showed deficiencies in: use of resources, innovation in sales techniques and interaction with the client; impacting business management. The strategies developed considered internal and external analysis, aligning them to the fulfillment of six strategic objectives of the company. The average monthly purchase increased from S / 442838 to s / 492644, increasing by 11.2%. The average purchase ticket went from S / 101.0 to S / 116.1 with an increase of 14.9%. The NPV was 200363, the IRR of 190.72% and a B / C 1.14 index demonstrating the financial economic viability of the strategic model implemented. The hypothesis test using the Mann-Whitney U determined that the median monthly sales revenue has a significant difference (p = 0.00 <0.05) between traditional management versus management with the strategic model implemented in the company.